Membrane material with electrochromism and energy storage functions, preparation method and color-changing energy storage device

By electrochemical synthesis of polyaniline film and combining metal oxide layers, the problem of difficult balance between electrochromic performance and capacitance performance of PANI materials is solved, and the electrochromic performance with high optical contrast and fast response is achieved, as well as high specific capacitance and cycling stability are achieved. energy storage performance.

CN119126451APending Publication Date: 2024-12-13JIANGSU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411192954.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-28
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

It is difficult for existing PANI materials to balance electrochromic performance and capacitive performance, resulting in the problem of excessive thickness or high cost of electrochromic layer.

Method used

Polyaniline films were prepared on conductive substrates by electrochemical synthesis method, combined with metal oxide layer, and electrical polymerization was performed by cyclic voltammetry of constant current and constant voltage, and the polymerization time was adjusted to obtain nanoparticle stacking structure, enhancing conductivity and specific capacitance , and at the same time, remove the reticular polyaniline layer to form a film material that has both electrochromic and energy storage functions.

Benefits of technology

Achieved 25% to 85% optical contrast and chromatic efficiency of 15cm2 C-1 to 35cm2 C-1 in visible light areas, with a color change response time of 0.05s to 5s and a conductivity of 10-3S cm-1 to 101S Within the cm-1 range, it has a specific capacitance of 400F g-1 to 850F g-1, and has good cycle stability and can exhibit multi-color characteristics at different potentials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119126451A_ABST
    Figure CN119126451A_ABST
Patent Text Reader

Abstract

The invention provides a membrane material with electrochromism and energy storage functions, a preparation method and a color-changing energy storage device, and belongs to the technical field of functional materials. According to the invention, the polyaniline film material with both electrochromic property and capacitance property is prepared on the conductive substrate through a method of combining electrochemical polymerization and post-treatment. The prepared polyaniline film material has the advantages of large number of discoloration, high response speed and high specific capacitance. The electrochromic material is prepared into an energy storage device, and an electrochromic energy storage device integrating electrochromism and energy storage can be formed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of functional materials, and relates to a film material having both electrochromic and energy storage properties, a preparation method, and a color-changing energy storage device. Background Art

[0002] Electrochromism is a phenomenon that can reversibly change its optical state (absorption, transmittance, reflectivity, etc.) under external voltage stimulation. Among them, materials with electrochromic properties are called electrochromic materials, which can undergo redox reactions under the action of an external electric field, and in this process, the optical properties and color of the material also change.

[0003] The device composed of electrochromic materials and other functional layers is called electrochromic device, which is mainly composed of electrochromic layer, electrolyte layer, ion storage layer and two transparent conductive electrodes. Electrochromic devices have many advantages such as no dead angle, no backlight, high contrast, low driving voltage, rich colors, wide operating temperature range and low manufacturing cost.

[0004] As one of the typical conjugated conductive polymers, polyaniline (PANI) has attracted extensive attention in the field of electrochemical energy storage due to its strong chemical structure adaptability, unique conductive behavior, simple synthesis, and eco-friendliness. Especially in the application of energy storage capacitors, PANI has a high conductivity of 2000 F g -1 The theoretical specific capacitance of PANI is therefore widely used in the manufacture of Faraday capacitors. In addition, PANI also has good electrochromic properties, including rich color changes (from transparent to yellow-green to blue-purple), low energy consumption, high optical contrast and fast response speed.

[0005] The Faradaic redox reaction of PANI is widely recognized as the basis for the electrochromic and capacitive behaviors of PANI. However, there is a clear trade-off between electrochromic and capacitive performance. Current literature shows that PANI materials with high specific capacitance usually exhibit relatively low optical contrast, and vice versa.

[0006] Although CN 114242466 B produces a supercapacitor dual-function material with both electrochromic function and high energy density, the electrochromic layer is too thick, resulting in unclear color change; and its preparation process involves silver plating using an evaporation method, which has a relatively complex process flow and high cost.

[0007] Although CN 114326242 A produces an enhanced electrochromic energy storage film, it uses silver nanowires as electrode materials, so the cost is relatively high.

[0008] Currently, balancing and optimizing the electrochromic and capacitive properties of PANI materials remains a major challenge. Summary of the invention

[0009] In order to overcome the deficiencies of the above-mentioned prior art, the present invention provides a film material and a preparation method having both electrochromic and energy storage functions, improving and balancing the electrochromic performance and capacitance performance of PANI materials; and an electrochromic energy storage device based on the dual-functional polyaniline film.

[0010] A method for preparing a film material having both electrochromic and energy storage functions, characterized in that it comprises the following steps:

[0011] S1. Cleaning of the conductive substrate: using a cleaning agent in an ultrasonic cleaner and rinsing with deionized water;

[0012] S2. Electrochemical synthesis of polyaniline: using high-purity platinum sheet, graphite, carbon cloth as counter electrode, Ag / AgCl, Hg / H2SO4, saturated calomel as reference electrode, acidic aniline solution as the main component of electrolyte, using constant current, constant voltage, cyclic voltammetry or one or more combinations thereof to electrochemically polymerize polyaniline (PANI) film on ITO / glass, the electropolymerization time ranges from 300s to 3000s;

[0013] S3. Post-treatment: removing the mesh polyaniline layer remaining on the surface of the polyaniline film, and obtaining the final aniline film having both electrochromic and energy storage functions after drying.

[0014] Furthermore, the cleaning agent in S1 is one or more of acetone, ethanol, and N-methylpyrrolidone.

[0015] Furthermore, the acidic aniline solution in S2 is a sulfuric acid-aniline mixed solution with a molar ratio of aniline to sulfuric acid of 0.2M:1M.

[0016] Furthermore, the electrochemical polymerization in S3 adopts a constant current method, and the constant current is 0.4 mA.

[0017] Furthermore, the drying in S3 is carried out in an oven at 30° C. for 1 hour.

[0018] Furthermore, before the electrochemical synthesis of polyaniline, the following steps are also included: preparing an electrochromic metal oxide layer on a conductive substrate by electrochemical polymerization or magnetron sputtering, wherein the electrochromic metal oxide layer is a WO3, NiO or MoO3 layer; and the prepared film is a composite film of polyaniline and metal oxide.

[0019] Furthermore, the conductive substrate is selected from ITO / glass, Au-Nylon66, and indium tin oxide (ITO) / glass.

[0020] The film material with both electrochromic and energy storage functions prepared by the preparation method is characterized in that the thickness of the polyaniline film is 150nm to 500nm, and the order of magnitude of the conductivity is in the range of 10 -3 S cm -1 Up to 10 1 S cm -1 , specific capacitance range is 400F g -1 Up to 850F g -1 ; Transparent, yellow, green, blue and purple colors can be displayed under applied potential, and the optical contrast in the visible light region is 25% to 85%; the coloring efficiency range is 15cm 2 C -1 Up to 35cm 2 C -1 ; The film color change response time is 0.05s to 5s.

[0021] The color-changing energy storage device based on the membrane material with both electrochromic and energy storage functions is characterized in that it is mainly composed of a polyaniline film or a composite film of polyaniline and metal oxide attached to a conductive substrate, a gel electrolyte and a conductive substrate, or is mainly composed of two polyaniline films or a composite film of polyaniline and metal oxide attached to a conductive substrate and a gel electrolyte, the gel electrolyte is coated on the polyaniline film or the composite film of polyaniline and metal oxide, and then the conductive substrate or the polyaniline film or the composite film of polyaniline and metal oxide attached to the conductive substrate is attached to the electrolyte layer and encapsulated with resin.

[0022] Furthermore, the gel electrolyte is prepared by the following method: 0.5 g of polymethyl methacrylate (PMMA) is added to 20 ml of acetone, and stirred until it is completely dissolved and the solution becomes transparent, then 1 g of polycarbonate (PC) and 0.5 g of lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) are added, and stirred at 400 rpm for 6 hours; after the gel electrolyte is coated on the polyaniline film, the acetone needs to be evaporated by drying, and then the polycarbonate PC is dripped onto the dried electrolyte, and then encapsulated.

[0023] During the electrochemical polymerization of polyaniline, as the polymerization time increases, the thickness of the polyaniline film no longer increases after 500 seconds, but the number and size of smaller nanoparticles increase, which helps to enhance the irregularity of the surface particle layer, ultimately leading to a larger surface area and a larger porosity; the polyaniline film obtained by electrochemical polymerization on ITO / glass using the chronopotentiostatic (constant current) technology has an outer surface with a loose porous network structure composed of nanorods.

[0024] In the post-treatment step after the electrochemical polymerization of polyaniline, a stacked structure with nanoparticles is formed on the outer surface of the polyaniline film after washing with deionized water, and its internal structure is characterized by a nanoparticle layer. Compared with the loose porous network structure composed of nanorods, it is more firmly connected to the surface of the substrate, and a porous surface composed of nanoparticles of different sizes is realized, thereby generating a surface morphology with high porosity and a significantly high specific surface area, providing the polyaniline film with optimal electrochromic and energy storage performance.

[0025] The PANI film prepared by the present invention has both electrochromic and energy storage functions, has a reversible electrochromic function, exhibits obvious multicolor characteristics under an applied potential, and exhibits different oxidation states and reduction states when scanning in different potential directions, thereby showing color changes. In the process of electrochemical synthesis of polyaniline of the present invention, the PANI films obtained after different polymerization times show similar color changes, and the color deepens with the extension of polymerization time, making the color transition more obvious when scanning the -1.0V to 1.0V cyclic potential, mainly the conversion between yellow and green. The present invention achieves more color changes, including transparent, yellow, green, blue and purple, by adjusting the electropolymerization time of the PANI film, showing the most color changes reported in the literature. An optical contrast of 25% to 85% is obtained in the visible light region; the coloring efficiency range is 15cm 2 C -1 Up to 35cm 2 C -1 The film material has a short color change response time ranging from 0.05s to 5s, and a fast response speed.

[0026] Moreover, as the polymerization time increases, a larger capacity and a longer charge and discharge time can be achieved. The conductivity of the membrane material ranges from 10 -3 S cm -1 Up to 10 1 S cm -1 , with high specific capacitance, the specific capacitance range is 400F g -1 Up to 850Fg -1 The energy storage capacity can be detected by color change, realizing the dual functional characteristics of electrochromic and energy storage. The membrane material has good cycle stability and still maintains the charging, discharging and color changing capabilities after more than 1,500 cycles.

[0027] Since the electrochromic property has a similar mechanism to that of supercapacitors, the prepared electrochromic / energy storage dual-function device has energy storage behavior, and its energy storage and release processes are accompanied by corresponding color changes, and its energy storage capacity can be detected by its appearance color. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a scanning electron microscope image of the indium tin oxide conductive glass / polyaniline (ITO / PANI) electrode prepared in Example 1 of the present invention, a1: surface before cleaning, a2: surface after cleaning, a3: cross section after cleaning.

[0029] Figure 2 3 is a photo of the indium tin oxide conductive glass / polyaniline (ITO / PANI) electrode prepared in Example 1 of the present invention, wherein (a) is the surface after cleaning and before wiping, and (b) is the surface after wiping.

[0030] Figure 3 The graph shows the color changes of the indium tin oxide conductive glass / polyaniline (ITO / PANI) electrode prepared in Example 1 of the present invention at different voltages.

[0031] Figure 4 This is a graph of the optical transmittance of the indium tin oxide conductive glass / polyaniline (ITO / PANI) electrode prepared in Example 1 in a colored / faded state.

[0032] Figure 5 This is a response time test chart of the indium tin oxide conductive glass / polyaniline (ITO / PANI) electrode prepared in Example 1 in the colored / faded state.

[0033] Figure 6 This is a constant current charge and discharge test diagram of the indium tin oxide conductive glass / polyaniline (ITO / PANI) electrode prepared in Example 1.

[0034] Figure 7 It is the cyclic voltammetry test diagram of the electrochromic / energy storage dual-functional polyaniline device prepared in Example 5 and the corresponding color changes under different voltages. DETAILED DESCRIPTION

[0035] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited thereto.

[0036] The mechanism of electrochromic energy storage of the polyaniline film material is that a small amount of sulfate ions are preferentially absorbed by some active sites on the PANI plane, and then a Faraday redox reaction and horizontal diffusion occur on the PANI surface, accompanied by changes in the valence state of the PANI. When the speed at which sulfate ions diffuse to the PANI surface is much faster than the speed of the electrochemical redox reaction, pseudo-capacitive charge storage occurs. Therefore, PANI can exhibit electrochemical properties similar to those of supercapacitors, such as a large specific capacitance. At the same time, PANI exhibits a stable and reversible electrochromic phenomenon during the surface Faraday redox reaction, and because the surface structure of PANI is relatively loose, the electrochemical active reaction area is large. Therefore, a large number of sulfate ions adsorbed or embedded on the PANI surface exhibit strong electronegativity, promote the protonation reaction of PANI, generate various polarons and bipolarons, increase the absorption of visible light, and gradually show color difference. With the increase of potential, the benzene unit in PANI is completely oxidized to a quinone unit, which enhances the visible light and near-infrared light absorption associated with the quinone electronic transition, resulting in a greater change in color difference and forming a richer color than before. Finally, a small portion of sulfate ions with higher energy migrated into the interior of PANI and gradually diffused.

[0037] Example 1

[0038] In a three-electrode electrolytic cell system, aniline (ANI, 4.66 g) was used as a monomer, sulfuric acid solution (H2SO4, 13.6 mL) was used as a supporting electrolyte, and a mixed solution with a monomer concentration of 0.2 mol / L and a supporting electrolyte concentration of 1 mol / L was prepared in a 250 mL volumetric flask as an electrolyte. An ITO / glass electrode was used as a working electrode, a platinum electrode was used as an auxiliary electrode, and a silver / silver chloride electrode was used as a reference electrode. At room temperature, a constant current method with a constant current of 0.4 mA and a duration of 500 s was used for electrochemical polymerization to obtain a polyaniline film on the ITO / glass working electrode. The loose polyaniline remaining on the surface was removed by eluting with deionized water, and the film was dried in an oven at 30°C for 1 hour to obtain an electrochromic energy storage polyaniline nanofilm. The surface micromorphology was tested by scanning electron microscopy, such as Figure 1 , Figure 2 As shown in the figure, a stacked structure with nanoparticles is formed on the outer surface of the polyaniline film after washing with deionized water, and its internal structure is characterized by a nanoparticle layer. Compared with the loose porous network structure composed of nanorods, it has a stronger connection with the substrate surface and realizes a porous surface composed of nanoparticles of different sizes, resulting in a high-porosity surface morphology and a significantly high specific surface area, providing the polyaniline film with the best electrochromic and energy storage performance.

[0039] Electrochromic and capacitive performance tests of electrochromic energy storage polyaniline nanofilms: The color change of the polymer film was tested by cyclic voltammetry; the visible light transmittance of the polymer film was tested and the contrast was calculated by UV-visible spectrophotometer; the response time of the polymer film was tested and calculated, and the capacitance was tested and calculated by electrochemical workstation. The results are as follows: Figure 3 , 4 , 5, and 6. Figure 3 It can be seen that when the voltage of -0.2V and 1V are applied to the electrochromic energy storage polyaniline nanofilm prepared in this embodiment, the color of the polymer film changes from transparent to yellow to green to blue and then to purple; Figure 4 , 5 It can be seen that when the voltages of -0.2V and 1V are applied to the electrochromic energy storage polyaniline nanofilm obtained in step (1), the electrochromic energy storage polyaniline nanofilm has a maximum contrast ratio of 48.29% at 580nm of the spectrum, a coloring time of 0.1s, and a fading time of 0.1s; Figure 6 It can be seen that the current density applied to the electrochromic energy storage polyaniline nanofilm obtained in step (1) is 0.2 mA g -1 When the current is 693F g -1 Specific capacitance.

[0040] Example 2

[0041] (1) In a three-electrode electrolytic cell system, aniline (ANI, 4.66 g) was used as a monomer, sulfuric acid solution (H2SO4, 13.6 mL) was used as a supporting electrolyte, and a mixed solution with a monomer concentration of 0.2 mol / L and a supporting electrolyte concentration of 1 mol / L was prepared in a 250 mL volumetric flask as an electrolyte. An ITO / glass electrode was used as a working electrode, a platinum electrode was used as an auxiliary electrode, and a silver / silver chloride electrode was used as a reference electrode. At room temperature, a constant current method with a constant current of 0.4 mA and a duration of 1000 s was used to carry out an electrochemical polymerization reaction to obtain a polyaniline film on the ITO / glass working electrode. The loose polyaniline remaining on the surface was removed by eluting with deionized water, and the film was dried in an oven at 30°C for 1 hour to obtain an electrochromic energy storage polyaniline nanofilm. The surface micromorphology was tested by scanning electron microscopy, which was consistent with the results of the experiment. Figure 1 resemblance.

[0042] (2) Testing of electrochromic and capacitive properties of electrochromic energy storage polyaniline nanofilm: testing the color change of the polymer film by cyclic voltammetry; testing the visible light transmittance and calculating the contrast of the polymer film by UV-visible spectrophotometer; testing and calculating the response time and capacitance of the polymer film by electrochemical workstation. When -0.2V and 1V voltages were applied to the electrochromic energy storage polyaniline nanofilm obtained in step (1), the color of the polymer film changed from transparent to yellow to green to blue and then to purple; when -0.2V and 1V voltages were applied to the electrochromic energy storage polyaniline nanofilm obtained in step (1), the electrochromic energy storage polyaniline nanofilm had a maximum contrast of 53.18% at 580nm of the spectrum, a coloring time of 0.7s, and a fading time of 0.5s; a current density of 0.2mA g was applied to the electrochromic energy storage polyaniline nanofilm obtained in step (1). -1 When the current is 617F g -1 Specific capacitance.

[0043] Example 3

[0044] (1) In a three-electrode electrolytic cell system, aniline (ANI, 4.66 g) was used as a monomer, sulfuric acid solution (H2SO4, 13.6 mL) was used as a supporting electrolyte, and a mixed solution with a monomer concentration of 0.2 mol / L and a supporting electrolyte concentration of 1 mol / L was prepared in a 250 mL volumetric flask as an electrolyte. An ITO / glass electrode was used as a working electrode, a platinum electrode was used as an auxiliary electrode, and a silver / silver chloride electrode was used as a reference electrode. At room temperature, an electrochemical polymerization reaction was carried out using a constant current method with a constant current of 0.4 mA and a duration of 1500 s to obtain a polyaniline film on the ITO / glass working electrode. The loose polyaniline remaining on the surface was removed by eluting with deionized water, and the film was dried in an oven at 30°C for 1 hour to obtain an electrochromic energy storage polyaniline nanofilm. The surface micromorphology was tested by scanning electron microscopy, which was consistent with the results of the experiment. Figure 1 resemblance.

[0045] (2) Testing of electrochromic and capacitive properties of electrochromic energy storage polyaniline nanofilm: testing the color change of the polymer film by cyclic voltammetry; testing the visible light transmittance and calculating the contrast of the polymer film by UV-visible spectrophotometer; testing and calculating the response time and capacitance of the polymer film by electrochemical workstation. When -0.2V and 1V voltages were applied to the electrochromic energy storage polyaniline nanofilm obtained in step (1), the color of the polymer film changed from transparent to yellow to green to blue and then to purple; when -0.2V and 1V voltages were applied to the electrochromic energy storage polyaniline nanofilm obtained in step (1), the electrochromic energy storage polyaniline nanofilm had a maximum contrast of 58.78% at 580nm of the spectrum, a coloring time of 1.0s, and a fading time of 0.7s; a current density of 0.2mA g was applied to the electrochromic energy storage polyaniline nanofilm obtained in step (1). -1 When the current is 622F g -1 Specific capacitance.

[0046] Example 4

[0047] (1) In a three-electrode electrolytic cell system, aniline (ANI, 4.66 g) was used as a monomer, sulfuric acid solution (H2SO4, 13.6 mL) was used as a supporting electrolyte, and a mixed solution with a monomer concentration of 0.2 mol / L and a supporting electrolyte concentration of 1 mol / L was prepared in a 250 mL volumetric flask as an electrolyte. An ITO / glass electrode was used as a working electrode, a platinum electrode was used as an auxiliary electrode, and a silver / silver chloride electrode was used as a reference electrode. At room temperature, a constant current method with a constant current of 0.4 mA and a duration of 2000 s was used to carry out an electrochemical polymerization reaction to obtain a polyaniline film on the ITO / glass working electrode. The loose polyaniline remaining on the surface was removed by eluting with deionized water, and the film was dried in an oven at 30°C for 1 hour to obtain an electrochromic energy storage polyaniline nanofilm. The surface micromorphology was tested by scanning electron microscopy, which was consistent with the results of the experiment. Figure 1 resemblance.

[0048] (2) Testing of electrochromic and capacitive properties of electrochromic energy storage polyaniline nanofilm: testing the color change of the polymer film by cyclic voltammetry; testing the visible light transmittance and calculating the contrast of the polymer film by UV-visible spectrophotometer; testing and calculating the response time and capacitance of the polymer film by electrochemical workstation. When -0.2V and 1V voltages were applied to the electrochromic energy storage polyaniline nanofilm obtained in step (1), the color of the polymer film changed from transparent to yellow to green to blue and then to purple; when -0.2V and 1V voltages were applied to the electrochromic energy storage polyaniline nanofilm obtained in step (1), the electrochromic energy storage polyaniline nanofilm had a maximum contrast of 59.96% at 580nm of the spectrum, a coloring time of 1.0s, and a fading time of 0.8s; a current density of 0.2mA g was applied to the electrochromic energy storage polyaniline nanofilm obtained in step (1). -1 When the current is 2.5 , the electrochromic energy storage polyaniline nanofilm has a power of 721F g -1 Specific capacitance.

[0049] Example 5

[0050] (1) First, 0.5 g of polymethyl methacrylate (PMMA) was added to 20 ml of acetone and stirred until completely dissolved. Then, when PMMA was completely dissolved and the solution became transparent, 1 g of polycarbonate (PC) and 0.5 g of lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) were added and stirred at 400 rpm for 6 h. Then, a layer of Li-PC / PMMA gel electrolyte was applied on the central area of ​​the surface of the ITO-PANI electrode, leaving a distance of 0.1 mm at the edge for encapsulation. It was then dried for 24 h to evaporate the acetone. PC was then dripped onto the dried electrolyte, the ITO-PANI electrode and the counter electrode (ITO / glass) were connected, and epoxy resin was dripped on the edge for encapsulation. Finally, it was placed in a vacuum drying oven for 12 h to evaporate all the remaining solvents to complete the assembly of the electrochromic energy storage device.

[0051] The electrochromic energy storage device obtained in this example was subjected to a cyclic voltammetry test to observe that the color of the device changes with the capacity when different voltages are applied. Figure 7 As shown, specifically, from -1V to 1V, the color changes from light gray to gray-green and then to blue-gray.

[0052] The embodiments are preferred implementations of the present invention, but the present invention is not limited to the above-mentioned implementations. Any obvious improvements, substitutions or modifications that can be made by those skilled in the art without departing from the essential content of the present invention belong to the protection scope of the present invention.

Claims

1. A method for preparing a polyaniline film having both electrochromic and energy storage functions, characterized in that: The following steps are involved: S1. Cleaning the conductive substrate: cleaning with a cleaning agent in an ultrasonic cleaner and rinsing with deionized water; wherein the conductive substrate is selected from ITO / glass, FTO / glass or Au-Nylon66; S2. Electrochemical synthesis: using high-purity platinum sheet and graphite as counter electrodes, one of Ag / AgCl, Hg / H2SO4, and saturated calomel as reference electrodes, and acidic aniline solution as the main component of the electrolyte, electrochemically polymerizing polyaniline (PANI) thin film on ITO / glass by one or more combinations of constant current, constant voltage, and cyclic voltammetry, with the electropolymerization time ranging from 300s to 3000s; S3. Post-treatment: removing the mesh polyaniline layer remaining on the surface of the polyaniline film, and obtaining the final aniline film having both electrochromic and energy storage functions after drying.

2. The method for preparing a polyaniline film having both electrochromic and energy storage functions according to claim 1, characterized in that: The cleaning agent in S1 is one or more of acetone, ethanol, and N-methylpyrrolidone.

3. The method for preparing a polyaniline film having both electrochromic and energy storage functions according to claim 1, characterized in that: The acidic aniline solution in S2 is a sulfuric acid-aniline mixed solution with a molar ratio of aniline to sulfuric acid of 0.2M:1M.

4. The method for preparing a polyaniline film having both electrochromic and energy storage functions according to claim 1, characterized in that: The electrochemical polymerization in S3 adopts a constant current method, and the constant current is 0.4 mA.

5. The method for preparing a polyaniline film having both electrochromic and energy storage functions according to claim 1, characterized in that: The drying in S3 is carried out in an oven at 30° C. for 1 hour.

6. The method for preparing a polyaniline film having both electrochromic and energy storage functions according to any one of claims 1 to 5, characterized in that: The following steps are also included: First, an electrochromic metal oxide layer is plated on an ITO / glass, FTO / glass or Au-Nylon66 conductive substrate by electrochemical polymerization or magnetron sputtering, and the metal oxide layer is WO3, NiO or MoO3; secondly, polyaniline is electrochemically polymerized on the electrochromic metal oxide layer, and finally a composite film of polyaniline and metal oxide is prepared.

7. A polyaniline film having both electrochromic and energy storage functions prepared by the preparation method according to any one of claims 1 to 5, characterized in that: The thickness of the polyaniline film is 150nm to 500nm, and the order of magnitude of the conductivity is in the range of 10 - 3 Scm -1 Up to 10 1 S cm -1 , specific capacitance range is 400F g -1 Up to 850F g -1 ; Transparent, yellow, green, blue and purple colors can be displayed under applied potential, and the optical contrast in the visible light region is 25% to 85%; the coloring efficiency range is 15cm 2 C -1 Up to 35cm 2 C -1 ; The film color change response time is 0.05s to 5s.

8. A color-changing energy storage device based on the polyaniline film having both electrochromic and energy storage functions as claimed in claim 7, characterized in that: It mainly consists of a polyaniline film attached to indium tin oxide (ITO) / glass, a gel electrolyte and indium tin oxide (ITO) / glass, or two polyaniline films attached to indium tin oxide (ITO) / glass and a gel electrolyte. The gel electrolyte is coated on the polyaniline film, and then the indium tin oxide (ITO) / glass or the polyaniline film attached to indium tin oxide (ITO) / glass is attached to the electrolyte layer and encapsulated with resin.

9. The color-changing energy storage device according to claim 8, characterized in that: The gel electrolyte is prepared by the following method: 0.5 g of polymethyl methacrylate (PMMA) is added to 20 ml of acetone, and stirred until it is completely dissolved and the solution becomes transparent, then 1 g of polycarbonate (PC) and 0.5 g of lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) are added, and stirred at 400 rpm for 6 hours; after the gel electrolyte is coated on the polyaniline film, the acetone needs to be evaporated by drying, and then the polycarbonate PC is dripped onto the dried electrolyte, and then encapsulated.